Examining the International Location of Arabic Literature and Culture Politics: King Oscar II’s Prize as a Case Study - Sarhan, Haitham (Al-Adab Journal, 2021)
Arabic Literature has occupied a prominent position within world cultures, both past and present. In the past the literature reflected Arabs’ impact on medieval civilizations, starting from the emergence of Islam and the spread of Arabic language outside of Arabia. Following the death of the Prophet Muhammad (PBUH), Arabic literature became the repertoire of knowledge, values, and identities that were produced in countless pieces of poetry, prose, tales, fables, speeches, and letters.This paper argues that throughout history there has been an inextricable relationship between Arabic literature and the type of politics that Muslims have produced, enabling them to spread the message of Islam and expand beyond their immediate geographical locations. Similarly, the various religious, language, and political contributions of Muslims in the few decades following the emergence of Islam have transformed Arabic literature into a pillar of world cultures, leading many non-Arabs to be attracted to and captivated by it.A modern manifestation of this captivation is exemplified by the prize initiated by King Oscar II of Sweden and Norway, who established an Academy of oriental languages in the 19th century. In consultation with Sultan Abdul Hamid II and the men of letters in Istanbul, the academy started a prize dedicated to Arabic literature and culture. The prize was won by prominent figures of Arabic literature at that time, including Iraq’s Mahmud Shukri al-Alusi and Mauritania’s Muhammad Mahmud al-Shanqiti.This paper will examine the context behind this almost forgotten episode of the interaction between Arabic and Western literatures and cultures, arguing that this prize can be seen as a precursor to the current discussion concerning Arabic literature in world literature paradigm.